Comparative effectiveness of antiepileptic drugs in patients with mesial temporal lobe epilepsy with hippocampal sclerosis. (31st August 2017) - Androsova, Ganna; Krause, Roland; Borghei, Mojgansadat; Wassenaar, Merel; Auce, Pauls; Avbersek, Andreja; Becker, Felicitas; Berghuis, Bianca; Campbell, Ellen; Coppola, Antonietta; Francis, Ben; Wolking, Stefan; et al.
Summary: Objective: Mesial temporal lobe epilepsy with hippocampal sclerosis (MTLE‐HS) is a common epilepsy syndrome that is often poorly controlled by antiepileptic drug (AED) treatment. Comparative AED effectiveness studies in this condition are lacking. We report retention, efficacy, and tolerability in a cohort of patients with MTLE‐HS. Methods: Clinical data were collected from a European database of patients with epilepsy. We estimated retention, 12‐month seizure freedom, and adverse drug reaction (ADR) rates for the 10 most commonly used AEDs in patients with MTLE‐HS. Results: Seven hundred sixty‐seven patients with a total of 3, 249 AED trials were included. The highest 12‐month retention rates were observed with carbamazepine (85.9%), valproate (85%), and clobazam (79%). Twelve‐month seizure freedom rates varied from 1.2% for gabapentin and vigabatrin to 11% for carbamazepine. Response rates were highest for AEDs that were prescribed as initial treatment and lowest for AEDs that were used in a third or higher instance. ADRs were reported in 47.6% of patients, with the highest rates observed with oxcarbazepine (35.7%), topiramate (30.9%), and pregabalin (27.4%), and the lowest rates with clobazam (6.5%), gabapentin (8.9%), and lamotrigine (16.6%). The most commonly reported ADRs were lethargy and drowsiness, dizziness, vertigo and ataxia, and blurred vision and diplopia. Significance: Our results did not demonstrate any clear advantage of newer versus older AEDs. Our results provide useful insights into AED retention, efficacy, and ADR rates in patients with MTLE‐HS.